PENGARUH PENGENDALIAN INTERN, KEPATUHAN DAN KOMPENSASI MANAJEMEN TERHADAP PERILAKU ETIS KARYAWAN (STUDI KASUS PADA PT ENSEVAL PUTERA MEGATRADING TBK PUSAT) - Sidauruk, Tagor Darius; Suci Lestari (Pasca Sarjana Universitas Satya Negara Indonesia, 2016)
This study aims to determine the effect of internal control, compliance, compensation management to ethical behavior of employees Center of PT Enseval Putera Megatrading Tbk. This study uses primary data obtained from questionnaires to the respondents. The sampling method used is purposive sampling and data that meet the criteria are as many as 60 samples. Multiple linear analysis is a technique of data analysis used in this study. The results obtained showed that partial internal control does not affect the ethical behavior of employees, compliance affect the ethical behavior of employees and management compensation does not affect the ethical behavior does not affect the ethical behavior of employees Center of PT Enseval Putera Megatrading Tbk.